An Evaluation of Poems in English Taught to Indonesian Senior High School Students - Halma Zakiyah; Delvi Wahyuni (Universitas Negeri Padang, 2020)
This study aimed to analyse common themes found in the English poems taught to senior high school students. Theme is unstated main idea of a literary work The object of this study was the poems in English taken from textbooks. This is a content analysis research used in analyzing the poems taken from textbooks. The instrumentations of this research was the researcher myself.The findings of the research showed that not all the poems’ theme are related to the teenage life as what Curriculum 2013 required. There were three poems which related to teenage life and fullfil the demand of Curriculum 2013.